OWN AND OTHER: CONTENT AND METHODOLOGY OF TRADITIONAL CULTURE IN PRIMARY EDUCATION - Siliņa-Jasjukeviča, Gunta; Rancāne, Aīda (Via Latgalica, 2017)
At the given moment, the traditional exists in a post-functional situation – many traditions are not getting inherited from generation to generation. If traditions are not transferred by acknowledging the old ones and by expressing them anew – they simply disappear. The freedom of a person to “carry out” his or her affiliation to a certain cultural space gets endangered. How can it be possible to strengthen one’s local, Latgalian cultural capital by learning and comprising the traditions of other regions of Latvia?The aim of the study is to draw attention to the issue of learning the traditional culture within the margins of primary education in regions of Latvia, including Latgale by actualizing the discussion about the importance of preparing contemporary teaching aids for acquisition of the traditional culture and language within different primary school subjects. In the article, the functioning of traditions and their learning is analysed by using the opposing terms “one’s own – alien/ different” as a universal, persistent notion in the binary worldview, by inviting to see within the alien not only the destructive, the opposite to one’s own, but also the forces that initiate the getting to know of the different, and allow it to become useful, usable, or refutable. A conceptual insight is offered within the context of the issue of creating a learning aid and selecting and arranging the content of Latvian regional traditions for the said aid in order to carry out a meaningful primary education for a student.The contraposition of terms “one’s own – other” is analysed as a universal, durable notion in the binary worldview. “The other begins, where one’s own ends, and this boundary moves along with the person” (Байбурин 1993: 185). One tends to see in the other not only the destructive, the contrary to one’s own, but also the powers that have initiated the creation of person’s world. In modern culture, the opposition of “one’s own – other” is being replaced by the opposition “one’s own – different” by getting to know the different, it can be allowed to become useful, applicable or rejectable.To arrange the surroundings of a person in the manner of a world, first a home is needed. To reside means to be somewhere familiar and intimate, in one’s own territory, and it is indispensable in order to specify oneself, to aggregate oneself. It is also a place where an encounter happens with the other, the different. On the other hand, often it is the different that allows one to perceive oneself as a unique entity and to recover one’s identity amidst the many changes and transformations.Learning the traditional culture of one’s region in the family and school is residing, being together with one’s own culture. Recognition of that which is one’s own, getting to know it, remembering it is an important condition for building one’s identity, which begins in childhood.A mechanical reproduction of the forms of traditional culture is useless. With the intermediation of personal meaningfulness, the socially significant norms and cultural values are made tangible in the mind of an individual and turn into inner motives of his or her actions and behaviour.It is important for the modern person to understand the traditional mechanism of thought, the system of perceptions and rituals, the reason behind them by using critical thinking already before beginning to learn about traditions, thus approaching the spiritual horizons of the archaic. By getting to know the different, it can become useful, applicable or rejectable.Within the concept of the content of the traditional culture it is important to respect the concepts and the principles that characterize every era and its society in general. Those are: time, space, participants, rituals, and results. The traditional culture can be incorporated in learning every area of basic education – the content of all subjects: languages, basics of technology and sciences, art, man and society. Traditional festivities offer the systemic and systematic option of absorption of the diversity of cultural traditions by using the content of different subjects of the basic education as a meaningful tool. Within this kind of education the artificially created margins of subjects disappear – life is reflected as a whole.Modern didactic concepts in creating useful insights suitable for learning the traditional culture are found in the empirical approach and action theory (Dewey 1979; Gill, Brockbank 2004; Griffin, Holford, Jarvis 2003; Kolb 2000; Леонтев 2005) that accentuates the significance of the personal experience and activity of an individual in constructing a new experience and comprehension, in the theories of personal development accentuating the part society and cultural space play in the process of the becoming of a personality (Bronfenbrenner 1989; Rogoff 2003), in the critical thinking approach the use of which in the education of an individual provides them with a deeper understanding of the changing reality (Kolb 2000; McWilliam, Taylor 2012). Experience about one’s regional traditional culture can be obtained in a theoretical and cognitive way, but the true depth of the cultural awareness is revealed only, when those traditions are being applied. Celebrations consolidate people of different generations within a common experience. By celebrating together with those close to child, that child will not question the importance of traditions. Learning by cooperating with people from different generations is one of the most important principles in the practice of the traditional culture. The meaningful understanding forms easier if a practical activity with a specific material takes place within a specific environment. Experience strengthens the connections to the surrounding world.